(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2019)
The study of the culture of peace in university contexts must be analyzed from an intercultural approach. The objective of this text is to present to the reader a reflection of the culture of peace as a deeper category, beyond an idea of the absence of conflict, is the enhancement in conflict scenarios. Conflicts are part of human relationships, it must be thought that the culture of peace goes beyond believing that there is no differentiated relationship, but that it should be understood as a means of resolving moments of rupture. This manuscript has been constituted from the experience in teaching for more than 30 years in Higher Education, contrasting the contextual reflections to the theoretical approaches, which support the expression and construction of the knowledge presented.